Anticardiolipin Antibody titer in pregnant women with preeclampsia and healthy women: A Case-Control Study - Darya Najafi; Saeedeh Sarhadi; Farahnaz Farzaneh (Mashhad University of Medical Sciences, 2022)
Introduction: Given the high prevalence of severe preeclampsia and its complications and the conflicting reports on the role of antiphospholipid antibodies, especially anti-cardiolipin, this study was performed aimed to compare the anti-cardiolipin antibody titer in pregnant women with preeclampsia and control group.Methods: In this case-control study, 220 pregnant women in the third trimester of pregnancy who referred to Ali ibn-e Abitaleb Hospital in Zahedan in 2012 were evaluated in two groups of pregnant women with preeclampsia and control group.  4 cc of blood samples were taken from all the women under study and sent to the laboratory for   tests under standard conditions. Anticardiolipin IgG and IgM levels were determined by ELISA method. Data were analyzed by SPSS (version 19) and Mann-Whitney test. P<0.05 was considered statistically significant.Results: In the present study, the mean IgM antibody titers in pregnant women with severe preeclampsia were 1.0±856.842 mg/L and in the control group 2.1±215.610 mg/L which was not significantly different between the two groups (P=0.531). Mean IgG antibody titers were also 2.1±468.163 mg/L in pregnant women with severe preeclampsia and 2.139±0.545 mg/L in the control group which was not significantly different between the two groups (P=0.345).Conclusion: In this study, no correlation was found between the levels of anti-cardiolipin antibody titers in pregnant women with preeclampsia compared with normal pregnant women.